Lipoprotein (a) and the risk of elevated depressive symptoms: The Multi-Ethnic Study of Atherosclerosis. (January 2021) - Hui, Nicholas; Morris, Margaret J.; Allison, Matthew A.; Tsai, Michael Y.; Rye, Kerry-Anne; Tabet, Fatiha; Ong, Kwok Leung
Abstract: Previous studies suggested a potential relationship between plasma lipoprotein (a) [Lp(a)] and elevated depressive symptoms. We aimed to investigate any such relationship in the Multi-Ethnic Study of Atherosclerosis participants who were free of cardiovascular events. Analysis included 4938 participants without elevated depressive symptoms and with Lp(a) levels measured at baseline. Participants were examined at four clinic visits over a 10-year period. Elevated depressive symptoms were assessed by the Center for Epidemiologic Studies Depression Scale (CES-D) and were defined as a CES-D score ≥16 or use of anti-depressants. Lp(a) level was measured with a latex-enhanced turbidimetric immunoassay. After adjusting for demographics, socioeconomic factors and other confounding factors in Cox regression analyses, a higher ln-transformed Lp(a) level was associated with new elevated depressive symptoms since baseline (hazard ratio [95% CI] = 1.09 [1.02–1.16] per SD increment in ln-transformed level, P  = 0.01). However, no association was found when elevated Lp(a) levels were assessed using clinical cut-off point (≥30 or 50 mg/dL), nor in sensitivity analyses using alternative definitions of elevated depressive symptoms. No significant interaction with race/ethnicity was found for all the above analyses. Also, no significant association was found between baseline Lp(a) levels and absolute or relative changes in CES-D score between baseline and last follow-up visits. Our study suggests a potential association between Lp(a) level and new elevated depressive symptoms, but such association was not robust in the sensitivity analyses. Future studies are warranted to investigate the role of Lp(a) in depressive symptoms in other cohorts. Highlights: There was no robust association between baseline Lp(a) and new depressive symptoms. No race/ethnicity interaction was found for new depressive symptoms. Baseline Lp(a) levels were not associated with change in CES-D score.